Implementasi Perlindungan Koleksi di Perpustakaan Universitas Sriwijaya Perspektif Undang-Undang Hak Cipta - Novita Vitriana; Dies Meirita Sari; Beta Ria Febrianti (Perpustakaan Universitas Gadjah Mada, 2026)
This study aims to analyze the implementation of Law Number 28 of 2014 concerning Copyright in protecting collections at the Library of Sriwijaya University and to identify the obstacles encountered in its implementation. The study is motivated by the increasing digitalization of library collections, which facilitates access to information but also has the potential to cause copyright infringements on scientific works and digital collections. The research employed a descriptive method with a quantitative approach. The population consisted of 10 librarians at the Library of Sriwijaya University, Indralaya Campus, using a total sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, and then analyzed using descriptive quantitative analysis through mean calculation. The results showed that the implementation of collection protection has referred to the provisions of the Copyright Law, particularly regarding reproduction, distribution, and the utilization of copyrighted works for educational and research purposes. Protection measures were carried out through restricting access to digital collections, implementing the fair use principle, using Turnitin to prevent plagiarism, and collaborating with publishers and copyright holders in providing legal digital collections. The main obstacles include users’ low understanding of copyright, limitations in technological infrastructure, and the lack of optimal socialization and education regarding the use of digital collections in accordance with legal provisions.